Femoral Neck Aspiration Aids in the Diagnosis of Osteomyelitis In Children With Septic Hip. Issue 10 (November 2018) - Schlung, Jedidiah E.; Bastrom, Tracey P.; Roocroft, Joanna H.; Newton, Peter O.; Mubarak, Scott J.; Upasani, Vidyadhar V.
Abstract : Background: The role of femoral aspiration (FA) in the treatment of septic arthritis of the hip is controversial. The purpose of this study was to determine if FA conducted concomitantly with irrigation and debridement (I&D) of the septic hip aids in microorganism and osteomyelitis identification and alters the treatment plan, or if the risks of the procedure outweigh its potential benefit. We also compare preoperative magnetic resonance imaging (MRI) with FA for diagnosis of osteomyelitis cooccurring with septic arthritis. Methods: Retrospective review was performed of all patients treated at a single institution between January 2003 and June 2014 for suspected septic hip arthritis. Eighty-three patients were identified with suspected or confirmed septic arthritis and 28 patients (33%) had cooccurring osteomyelitis. Demographic and clinical data were recorded for each patient. The sensitivity and specificity of FA and MRI for diagnosing osteomyelitis were determined. Results: Among the 83 patients with confirmed or suspected septic arthritis, 31 patients (37%) had a FA performed at the time of the hip I&D, resulting in positive cultures in 17 patients. All of these patients had other positive cultures (blood and/or joint fluid) that grew the same organism. 54 patients (65%) had a preoperative MRI. The MRI was falsely negative in 10 patients, 6 of whom had a positive FA resulting in appropriate management of osteomyelitis. Missed or delayed diagnosis of osteomyelitis resulted in significant morbidity in 3 patients (avascular necrosis and femoral neck fracture, extensive lower extremity osteomyelitis, and subtrochanteric fracture with malunion). No complications associated with FA were identified. FA and MRI were found to have sensitivity/specificity for osteomyelitis of 100%/100% and 38%/95%, respectively. Conclusions: Although FA did not improve microorganism identification, it did aid in the diagnosis of cooccurring osteomyelitis when treating children with septic arthritis, especially in patients with false negative MRI findings for osteomyelitis. We recommend FA at the time of septic hip I&D as its benefits appear to far outweigh its risks. Level of Evidence: Level III— diagnostic study.